Accounting regulatory issues on investments in Islamic bonds - Abdul Rahman, Abdul Rahim (International Institute of Islamic Business and Finance, 2003)

(untitled)
The main objective of this paper is to examine contemporary accounting regulatory issues on investments in Islamic bonds or sukuk. Investments on Islamic bonds (sukuk) give rise to a number of accounting and reporting issues related to recognition, measurement and disclosure. The underlying rationale of this paper is that proper development of Islamic financial market requires a well regulated Islamic financial instruments and one of the key elements of regulation is accounting regulation. Therefore, a well regulated Islamic financial market requires a sound accounting and reporting standard of Islamic financial instruments that, first, meet the requirements of syari’ah, and, second, relevant to be practiced in our time. The need for Islamic accounting that deals with Islamic financial instruments has prompted AAOIFI recently to introduce Financial Accounting Standard No.17 on investments in securities ( AAOIFI FAS 17, 2003). The need for a codified Islamic accounting standard are primarily stemmed from the need that Islamic accounting objectives, concepts and principles to be developed based on syari’ah requirements. However, the Islamic accounting regulation also needs to adapt to the modern accounting regulatory environment to make it relevant to be practiced in our time. The examination of AAOIFI FAS 17 shows that AAOIFI has been pragmatic in its approach by considering both requirements when developing its standard. This is a pro-active step to provide a sound accounting regulation as part of a comprehensive regulation of Islamic financial institutions.